The role of the intensive care nurse in antimicrobial stewardship: systematic review - Brandão, Marina (2024)
Introduction: Nowadays there has been a rise in the incidence of antimicrobial-resistant microorganisms. It’s important to involve every member of the interdisciplinary team in the investment of strategies that promote an adequate use of antimicrobials, particularly in the critically ill patient. Objective: To determine the role of the intensive care nurse in antimicrobial stewardship. Methods: A systematic review of the literature was conducted on the EBSCO Discovery Service platform and the Scopus and SciELO databases, using health science descriptors and key words. The research question was developed using the PICO strategy and the articles were selected by two independent reviewers using the PRISMA methodology. Results: 9 articles were selected and analyzed. 7 categories emerged: review of the antimicrobial prescription; collection of samples with critical thinking; monitoring the critically ill and administration of antimicrobials; identification of allergies; implement infection control precautions; health education; and leadership and communication. Conclusion: The nurses that work in intensive care units implement interventions that promote an adequate use of antimicrobials. However, in order to better define their role and improve their involvement in the multidisciplinary team, there is a need to conduct more studies